Effects of an adiabatic inclined fin on the mixed convection heat transfer in a square cavity - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Inderscience Enterprises Ltd, 2014)
In this study, a square cavity with two ventilation ports in the presence of an adiabatic fin placed on the bottom wall of the cavity is numerically analysed for the mixed convection case for a range of Richardson numbers (Ri = 0.1,1, 10, 30) and at Reynolds number of 300. The top and bottom walls of the cavity are kept at constant temperature while the verticals walls are assumed to be adiabatic. The effect of the fin height, inclination angle and Richardson number on the fluid flow and heat characteristics is numerically analysed. The results are presented in terms of streamlines, isotherm plots and averaged Nusselt number plots. It is observed that length and inclination angle of the fin significantly alter the streamlines and isotherms and hence the thermal performance of the system. For the best performance at different fin lengths, optimum inclination angle changes.
Keywords: mixed convection; adiabatic fin; thermal performance